Bougainvillea glabra Choisy (Nyctinaginacea): review of phytochemistry and antimicrobial potential - Ornelas García, Ingrid G.; Guerrero Barrera, Alma L.; Avelar González, Francisco J.; Chávez Vela, Norma A.; Gutiérrez Montiel, Daniela (Frontiers in Chemistry, 2023)
The Bougainvillea glabra or bougainvillea is a climbing plant native from South America belonging to the Nyctaginaceae family. The bougainvillea is recognized worldwide for its horticultural importance, due to the color of its bracts, commonly known as "flowers", made up of bracts, which are the striking parts, and the true flowers, which are white and small. Bougainvillea is widely known in traditional medicine to treat respiratory diseases such as cough, asthma, and bronchitis, gastrointestinal diseases, also for its antibacterial and insecticidal capacity. The antimicrobial potential of the involucre of this plant has not been studied, despite research showing a high phytochemical presence of secondary metabolites such as alkanes, phenols, terpenes, and betalains. This review compiles Running Title 2 information about the traditional uses of B. glabra, its botanical description, ecological relevance, phytochemistry, antimicrobial and antibiofilm activity, such as the toxicology of bracts and flowers.